MODEL PEMBERDAYAAN PEREMPUAN BERBASIS PESANTREN: STUDI KASUS PONDOK PESANTREN SUNAN GUNUNG JATI BA'ALAWY - Atika Sri Devi; Moh. Yasir Alimi (Sociology of Religion Study Program, Faculty of Social Sciences, North Sumatra State Islam, 2025)
This study aims to analyze the pesantren-based women's empowerment model at the Sunan Gunung Jati Ba'alawy Islamic Boarding School and examine the strategic role of Ibu Nyai as a central figure in building the spiritual, intellectual, and social independence of female students. The research uses a descriptive qualitative approach with a case study method, through data collection techniques in the form of in-depth interviews, participatory observation, and documentation.The results show that women's empowerment in this Islamic boarding school is implemented through four main pillars, namely: (1) spiritual empowerment through the Al-Qur'an memorization program, which fosters discipline and religious character; (2) intellectual empowerment through the study of classical Islamic texts, which trains critical thinking and reasoning; (3) socio-cultural empowerment through the Maulid Nabi tradition, which builds solidarity and collective leadership; and (4) leadership empowerment through the example set by Ibu Nyai, who combines charismatic, economic, and social responsibility values. This model reflects an alternative form of empowerment based on Islamic values and Islamic boarding school wisdom that is adaptive to the challenges of the times. Pesantren not only serve as religious educational institutions, but also as spaces for social transformation that prepare women to be empowered, independent, Islamic in character, and ready to contribute to sustainable community development.